Examining the Impact of Autonomous Robot Integration on Efficiency, Safety and Quality Towards Industrial Revolution 4.0 - Adam, Muhammad Aqil; Ismail, Siti Norziah (Research in Management of Technology and Business, 2025)
This research investigates the impact of integrating autonomous robots into manufacturing environments, specifically at Honda Malaysia Sdn Bhd, within the framework of Industry 4.0. As industries strive for enhanced efficiency, safety, and quality, autonomous robots emerge as crucial tools that automate labor-intensive, repetitive tasks while minimizing human error. The study employs a quantitative methodology, utilizing surveys distributed to engineers, technicians, and managers to assess the effects of robotic integration. Findings reveal that the deployment of autonomous robots significantly improves production efficiency, enhances workplace safety by reducing human exposure to hazardous tasks, and ensures product quality through consistent and precise operations. The results indicate that a substantial portion of the variation in robot implementation can be explained by these independent variables. While the advantages are evident, challenges such as sensor reliability and workplace dynamics require ongoing attention to ensure optimal performance and safety. The research underscores the necessity for strategic planning in workforce adaptation, emphasizing collaboration between humans and robots to foster innovation and maintain job relevance in the evolving industrial landscape. Ultimately, this study offers valuable insights for industry practitioners seeking to leverage autonomous technology for sustainable growth and competitiveness.